The Role of Digital Payments for School Management at Tadika Suria Edukids Center Malaysia - Ridatul Fitri; Isra Hayati (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study aims to determine the role of digital payment for school management at Tadika Suria Edukids Centre, Malaysia. This study is based on the importance of implementing digital technology in school financial management to improve efficiency, transparency, and accountability, especially in early childhood education institutions. This study uses a qualitative approach with data collection techniques through observation, interviews, and literature studies. The results of the study indicate that the use of a digital payment system can streamline the process of paying education fees, make it easier for parents to access financial information instantly, and support more structured and transparent school budget management. In addition, the transaction process takes place safely, orderly, and in accordance with sharia principles. Digital payment can be a strategic solution in modernizing school financial governance, while building trust between schools and parents. This study recommends the implementation of digital payment as part of management innovation in early childhood education institutions